Virulence properties and enterotoxin production of Aeromonas strains isolated from fish. - Santos, Y (1988)
The biological activities in vivo and in vitro of 59 motile Aeromonas spp. isolated from fish and water tanks were simultaneously analyzed in poikilothermic and homoiothermic systems. A total of 64.3% of the isolates tested were pathogenic for fish, and 62% of Aeromonas hydrophila and A. sobria isolates either virulent or nonvirulent for fish were enterotoxigenic. Although the majority of the strains were proteolytic and amylolytic and produced DNase, other activities, such as elastase and staphylolysis, were only present in A. hydrophila. Most of the strains (96%) produced hemolysins, and 68% had agglutinating capacity, but neither isolates pathogenic for fish nor enterotoxigenic isolates showed specificity for trout or human erythrocytes, respectively. The production of siderophores, agglutination in acriflavine, and precipitation after boiling were found not to be useful tests for screening virulent strains. Although statistical analysis revealed a significant relationship between virulence for fish and positive results for arabinose and sucrose fermentations, elastase, and hemolysis of human erythrocytes, only lysine decarboxylase showed a significant positive relationship with enterotoxigenicity. Using extracellular products from representative Aeromonas strains with different virulence markers and belonging to distinct O serogroups, we demonstrated a lack of correlation between cytotoxicity for fish and homoiothermic cell lines and pathogenicity. The extracellular products from selected pathogenic A. hydrophila strains were lethal for rainbow trout and displayed proteolytic, hemolytic, and cytotoxic activities which were simultaneously lost after heat treatment. The findings reported here indicate that it is not possible to establish a common and single mechanism involved in the invasion of Aeromonas spp. in poikilothermic and homoiothermic hosts.